LITERASI DIGITAL DALAM PENDIDIKAN ANAK USIA DINI DI KECAMATAN SAKETI KABUPATEN PANDEGLANG PROVINSI BANTEN - Hidayat, Amat; Muharomah, Dewi Robiatun; Putri, Vina Karina; Ramadhan, Muhamad Hanif; Mubarok, Ahmad; Jundi, Rachmatullah (STAI Darul Qalam Tangerang, 2023)
The use of technology in education is currently an important indicator in efforts to improve the quality of learning in early childhood (PAUD), especially in influencing the optimization of children's growth and development. This study aims to determine the impact of digital literacy on PAUD educators according to four indicators, namely access, selection, understanding, and dissemination of information. This research is a descriptive research using quantitative methods. The population includes all PAUD teachers from 8 institutions in Saketi District, totaling 30 people. The sampling technique uses a population sampling technique that includes all PAUD teachers in the Saketi sub-district. The results of the research data analysis show that the average value of digital literacy educators in PAUD is in the proper category. Therefore, the digital literacy of PAUD educators needs to be improved so that they can make better use of digital devices in their learning, in order to optimize children's growth and development